Dielectric Spectroscopy of Coking Coal with High Sulphur Content - Cai, Chuan-Chuan; Zhang, Ming-Xu; Min, Fan-Fei (Asian Journal of Chemistry, 2014)
Using reflection transmission method to measure the permittivity of coking coal from Shanxi province in the frequency range between 200-600 MHz. Results shows that the real part and imaginary part of dielectric constant of three coal samples all decreased with the increase of frequency. The loss tangent of raw coal and clean coal decreases with the increase of frequency. There is a good linear relationship between log e', log e" and log f by data fitting processing.